2022
DOI: 10.3390/vaccines10050752
|View full text |Cite
|
Sign up to set email alerts
|

Lineage 1 Porcine Reproductive and Respiratory Syndrome Virus Attenuated Live Vaccine Provides Broad Cross-Protection against Homologous and Heterologous NADC30-Like Virus Challenge in Piglets

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is an important pathogen that endangers the swine industry worldwide. Recently, lineage 1 PRRSVs, especially NADC30-like PRRSVs, have become the major endemic strains in many pig-breeding countries. Since 2016, NADC30-like PRRSV has become the predominant strain in China. Unfortunately, current commercial vaccines cannot provide sufficient protection against this strain. Here, an attenuated lineage 1 PRRSV strain, named SD-R, was obtained by passaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Signifcant diferences between two groups were determined using a t-test (and nonparametric tests) in GraphPad 5.0 (San Diego, CA, USA). Te level of signifcance was set at p < 0.05 [33].…”
Section: Discussionmentioning
confidence: 99%
“…Signifcant diferences between two groups were determined using a t-test (and nonparametric tests) in GraphPad 5.0 (San Diego, CA, USA). Te level of signifcance was set at p < 0.05 [33].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2016, NADC30-like PRRSV has become the major endemic strain in China ( 9 , 39 ). A candidate live attenuated vaccine (SD-R strain) against NADC30-like PRRSV was developed by our laboratory, which has higher safety, provides complete clinical protection for piglets against homologous and heterologous NADC30-like PRRSVs ( 32 ) and NADC34-like PRRSV (unpublished), and significantly improves daily weight gain and decreases viremia ( 32 ). Thus, SD-R could provide good protection against lineage 1 branch PRRSV.…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous cross-protection by most PRRS vaccines is an obvious deficiency and is also the focus of veterinary researchers. In a previous study, we developed an attenuated lineage 1 PRRSV vaccine (SD-R) that provides safe and effective protection against homologous NADC30-like PRRSV and heterologous NADC30-like PRRSV challenges ( 32 ). Furthermore, SD-R could provide effective protection against NADC34-like PRRSV (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that PRRSV loses its virulence due to adaptation to MARC-145 cells in vitro resulting in an attenuated phenotype in vivo ( 57 ). Furthermore, PRRS MLVs can be generated by in vitro passaging leading to attenuation ( 58 , 59 ). The LV strain has a 99.76% sequence homology to the PRRSV field isolate IVI-1173 (Genbank Accession number KX622783.1) that caused a PRRSV outbreak in Switzerland (2012) ( 60 ).…”
Section: Discussionmentioning
confidence: 99%